Deoxynucleoside Therapy for Thymidine Kinase 2–Deficient Myopathy. Issue 2 (17th June 2019) - Domínguez‐González, Cristina; Madruga‐Garrido, Marcos; Mavillard, Fabiola; Garone, Caterina; Aguirre‐Rodríguez, Francisco Javier; Donati, M. Alice; Kleinsteuber, Karin; Martí, Itxaso; Martín‐Hernández, Elena; Morealejo‐Aycinena, Juan P.; Munell, Francina; Nascimento, Andrés; et al.
Abstract : Objective: Thymidine kinase 2, encoded by the nuclear gene TK2, is required for mitochondrial DNA maintenance. Autosomal recessive TK2 mutations cause depletion and multiple deletions of mtDNA that manifest predominantly as a myopathy usually beginning in childhood and progressing relentlessly. We investigated the safety and efficacy of deoxynucleoside monophosphate and deoxynucleoside therapies. Methods: We administered deoxynucleoside monophosphates and deoxynucleoside to 16 TK2‐deficient patients under a compassionate use program. Results: In 5 patients with early onset and severe disease, survival and motor functions were better than historically untreated patients. In 11 childhood and adult onset patients, clinical measures stabilized or improved. Three of 8 patients who were nonambulatory at baseline gained the ability to walk on therapy; 4 of 5 patients who required enteric nutrition were able to discontinue feeding tube use; and 1 of 9 patients who required mechanical ventilation became able to breathe independently. In motor functional scales, improvements were observed in the 6‐minute walk test performance in 7 of 8 subjects, Egen Klassifikation in 2 of 3, and North Star Ambulatory Assessment in all 5 tested. Baseline elevated serum growth differentiation factor 15 levels decreased with treatment in all 7 patients tested. A side effect observed in 8 of the 16 patients was dose‐dependent diarrhea, which did not require withdrawal of treatment. Among 12 other TK2 patients treated with deoxynucleoside, 2 adults developed elevated liver enzymes that normalized following discontinuation of therapy. Interpretation: This open‐label study indicates favorable side effect profiles and clinical efficacy of deoxynucleoside monophosphate and deoxynucleoside therapies for TK2 deficiency. ANN NEUROL 2019;86:293–303